2019
DOI: 10.3389/fimmu.2019.02499
|View full text |Cite
|
Sign up to set email alerts
|

Junin Virus Triggers Macrophage Activation and Modulates Polarization According to Viral Strain Pathogenicity

Abstract: The New World arenavirus Junin (JUNV) is the etiological agent of Argentine hemorrhagic fever (AHF). Previous studies of human macrophage infection by the Old-World arenaviruses Mopeia and Lassa showed that while the non-pathogenic Mopeia virus replicates and activates human macrophages, the pathogenic Lassa virus replicates but fails to activate human macrophages. Less is known in regard to the impact of New World arenavirus infection on the human macrophage immune response. Macrophage activation is critical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…However, the different outcomes of chicken challenged with PmCQ2 and PmQ hint that macrophage may play different roles. For example, NOS2, a key marker, and PTX3 and IRF5, two important regulators of M1 macrophage activation (51)(52)(53), were significantly overexpressed in PmQ infected chicken, tending to activate to more pro-inflammatory activation. Whereas, in the PmCQ2 infected chicken lung, M2 markers (MRC1LD, MRC1LB, and MACRO) and M1 markers (CD86 and CD80) were upregulated, implying a mixed activation of both M1 and M2 macrophage occurred.…”
Section: Discussionmentioning
confidence: 99%
“…However, the different outcomes of chicken challenged with PmCQ2 and PmQ hint that macrophage may play different roles. For example, NOS2, a key marker, and PTX3 and IRF5, two important regulators of M1 macrophage activation (51)(52)(53), were significantly overexpressed in PmQ infected chicken, tending to activate to more pro-inflammatory activation. Whereas, in the PmCQ2 infected chicken lung, M2 markers (MRC1LD, MRC1LB, and MACRO) and M1 markers (CD86 and CD80) were upregulated, implying a mixed activation of both M1 and M2 macrophage occurred.…”
Section: Discussionmentioning
confidence: 99%
“…Although the role of miRNA in mammarenavirus pathogenesis is not clear, its role in regulating important molecular pathways during infection cannot be ruled out as an important mechanism to be further investigated. In addition, many studies have suggested that a multifactor pathway could be involved in the different outcomes from arenaviral infection including a relatively low number of adaptive mutations, as well as the incapacity to bind to human receptors and different immune responses elicited by these viruses [ 91 , 92 , 93 ].…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral blood mononuclear cells (PBMCs) were obtained from healthy volunteer donors who had given written consent and has not taken any non-steroidal anti-inflammatory drugs for 10 days prior to sampling, as previously described [ 5 , 8 , 32 ]. Briefly, PBMCs from healthy donors were isolated by Ficoll-Hypaque (GE, Chicago, IL, USA) density gradient centrifugation, and a positive selection of CD14+ monocytes was performed using an EasySep Human CD14 Positive Selection Kit (StemCell Tech, Vancouver, BC, Canada) as indicated by the manufacturer.…”
Section: Methodsmentioning
confidence: 99%